Gambaran Penggunaan Media Word Search terhadap Partisipasi Aktif Siswa dalam Pembelajaran Bahasa Indonesia - Haya Nisrina Afifah; Jesi Alexander Alim; Zakiah Ulya (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2025)
This study aims to describe the use of Word Search media in enhancing students’ active participation in Indonesian language learning. The background of this research lies in the low level of student engagement during classroom activities, which often tend to be passive, thus requiring innovative learning media to increase activeness. This research employed a descriptive quantitative method with 21 third-grade students of SD Negeri 184 Pekanbaru as the subjects. The research instrument was a student engagement questionnaire consisting of 10 indicators based on the dimensions of behavioral, emotional, and cognitive engagement. Data were analyzed using descriptive statistics by calculating the mean score of each indicator, which was then categorized into Very Good, Good, Fair, and Poor. The findings showed that most indicators were in the Good to Very Good categories, while only two indicators were categorized as Fair. These results indicate that the use of Word Search media can enhance students’ engagement in behavioral, emotional, and cognitive aspects. Therefore, it can be concluded that Word Search is an effective, innovative, and enjoyable learning medium to foster students’ active participation in Indonesian language learning.